(untitled) (Cyberspace: Jurnal Pendidikan Teknologi Informasi, 2022)
This research is purpose to develop a android application that can be a Aceh language learning media based on PAUD curriculum. Backgrounds of this research is a requirement of PAUD teacher media for learning Aceh language based on Aceh curriculum. This research using User Centered Design (UCD) for the method and system usability scale (SUS) method for apps usability test, the final result for this apps who tested on 20 respondent consist of 14 respondent from PAUD teacher, 3 respondent from lecture of PTI and 3 respondent from PAUD lecture is 79 score point, in the percentile rank graphic this application get B grade and based on adjective rank this apps get good rating, so thi]s app categorized as good apps cause already according to users need and easy to use for users